Dificuldades no processo da leitura e escrita dos discentes do 1º ano do ensino médio da escola Esmerina Boa-Habib no município de Abaetetuba-PA - CARDOSO, Rosinete de Lima (2023)
This work was carried out at Escola Estadual de Ensino Fundamental e Médio Esmerina Boa-Habib, with students in the 1st year of high school, with the aim of highlighting one of the problems that most affects students at academic age: Difficulties in the reading process and writing of students in the 1st year of high school at Escola Esmerina Boa-Habib in the municipality of Abaetetuba-PA. It can also be added that although many students move on to later grades, they still often do not know how to expose themselves through the oralization of reading written texts, showing insufficient development in the face of seminars, interviews, debates, theatrical presentations, among others. . During the execution of this work it can be observed that other factors also influence this reality, among them is the indifference of some families in encouraging their children to read. In addition, the school, which should also support teachers, leaves much to be desired, forgetting the commitment to this problem in teaching-learning. However, there are those who seek new pedagogical practices and, consequently, manage to achieve a favorable result for their students.